Pengaruh Disposisi Matematis Terhadap Kemampuan Pemecahan Masalah Matematis Siswa - Gisela Elfira Mayratih; Samuel Igo Leton; Irmina Veronika Uskono (Asimtot : Jurnal Kependidikan Matematika, 2019)
This study aims to determine the effect of students' mathematical dispositions on mathematical problem solving abilities of students in class VII of SMP. The type of research used is quantitative. The sample in this study was class VII A, amounting to 30 people who were selected using simple random sampling from 6 existing classes. The type of data in this research is primary data with data collection used using a disposition questionnaire consisting of 28 items and tests consisting of 5 items of description. Testing the hypothesis in this study using a simple regression test. After the data is analyzed the regression equation is obtained as follows: Y = 16,312 + 0.523X. before testing the hypothesis, the data normality test and linearity test were carried out. Based on the data analysis, it was found that the t-test = 3.296 with significance = 0.003 and table = 2.048. then t count = 3.296> 2.048 = t table means that data is normally distributed. To see the achievement of the disposition indicators of junior high school students in the junior high school class, the average of each indicator is calculated and the achievement of the mathematical disposition indicator is 50.08%. Whereas for grouping mathematical dispositions, problem solving abilities obtained the highest dispositions having an average of 63.04, moderate dispositions having an average of 43.56, and low dispositions having an average of 40.51. Thus, it can be concluded that there is an influence of mathematical disposition on mathematical problem solving abilities of students of junior high school class.